Attending an Academic Conference: Story of a First Time Attendee - Bhandari, Binaya (Journal of Education and Research, 2017)
This non-refereed contribution to the special issue of Journal of Education and Research portrays the reflective experiences of a novice researcher who attended the First International Conference on Transformative Education Research and Sustainable Development in Dhulikhel, Nepal, in October 2016. I begin by introducing my interest in participating in academic and scientific conferences, reflect upon the mentorship received during my Master of Philosophy study at Kathmandu University School of Education, examine my dual roles of a volunteer in conference organization and a poster presenter at the same conference, and share my impressions of the conference environment. I conclude with some final thoughts on how I could enlarge conference learning.